2022
DOI: 10.3389/fpubh.2022.794967
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Study of Early Childhood Care and Education Services Under the Age of Three: Evidence From Sichuan Province, China

Abstract: In China, early childhood care and education services for children under the age of three are neglected to some extent. Based on survey data from the Health Commission in Sichuan Province of China, this study analyzes the situation of early childhood care and education services in Sichuan through a qualitative method, using an analytical framework of matching the demand and supply. The findings reveal a mismatch between demand and supply of early childhood care and education services. This gap is likely to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…With the strengthening of policy guidance on infant and toddler care, research attention regarding this field is increasing. Some studies have revealed a mismatch between the demand and supply of infant and toddler care support [22,27]. However, previous studies have lacked a systematic theoretical framework for integrating types of infant and toddler care support comprehensively.…”
Section: Literature Review 21 Types Of Family Support For Infant and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…With the strengthening of policy guidance on infant and toddler care, research attention regarding this field is increasing. Some studies have revealed a mismatch between the demand and supply of infant and toddler care support [22,27]. However, previous studies have lacked a systematic theoretical framework for integrating types of infant and toddler care support comprehensively.…”
Section: Literature Review 21 Types Of Family Support For Infant and ...mentioning
confidence: 99%
“…Previous studies have investigated family support for childcare and parenting stress separately [7,20]. However, there is a lack of research in the context of the three-child policy [12,21], and previous studies have not considered the characteristics of family structure changes [22]. In addition, there is a lack of comprehensive analysis of infant and toddler care support from the perspective of the family, and the impact on parenting stress is also unclear.…”
Section: Introductionmentioning
confidence: 99%